Profesi Guru dalam Pandangan Yuridis - Devita Nanda Oktavia; Syalsabilla Zahira Yasmin Pertiwi; Putri Adzana Ramadhani; Muhammad Ridho Fadhilah; Ikmawati, Ikmawati (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
Any career or position that demands expertise which may come from specific education and training in compliance with unique standards, including duties and a code of ethics, is considered a profession. Positions in teaching are meaningful careers that call for specialised knowledge and abilities that are not available to people outside of the teaching profession. Encouraging teachers to be professional educators, managers, mentors, assessors, members of professional associations, and public relations experts are all goals of teacher professionalism. The research method used is literature study, a method of collecting reading sourcesthat will be used as references in research. Founded on Article 1 of Law of the Republic of Indonesia No. 14 of 2005 concerning Teachers and Lecturers In early childhood education through formal education, basic education, and secondary school, teachers' primary responsibilities as professionals in education are to instruct, guide, direct, train, assess, and evaluate students. Teaching, research, and community service are the primary means by which lecturers who are trained educators and scientists transform, develop, and spread science, technology, and the arts.